2020
DOI: 10.1177/1075547020914906
|View full text |Cite
|
Sign up to set email alerts
|

Science Communication Meets Consumer Relations: An Analysis of Twitter Use by 23andMe

Abstract: For-profit organizations play a considerable role in the dissemination of scientific research and information. In the case of direct-to-consumer genetic testing, this is important because how consumers learn about genetic science can influence health decisions and support for science. Through a content analysis of Twitter posts ( N = 1,000), this study examined how 23andMe balances traditional promotion, communicating product benefits, and sharing scientific research. Results indicated that about half of all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 32 publications
5
16
0
Order By: Relevance
“…The test purposes found in the videos largely resemble the most common genetic test purposes, with most videos talking about ancestry or relationship testing and fewer about trait and health testing. This finding is in line with previous research on YouTube videos related to DTC genetic testing [ 28 , 31 ] and social media in general [ 20 , 21 , 25 ]. Nonetheless, in contrast to our study, Yin et al [ 27 ] found in their collected Reddit data set that relationship and health testing were more often mentioned than ancestry testing.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The test purposes found in the videos largely resemble the most common genetic test purposes, with most videos talking about ancestry or relationship testing and fewer about trait and health testing. This finding is in line with previous research on YouTube videos related to DTC genetic testing [ 28 , 31 ] and social media in general [ 20 , 21 , 25 ]. Nonetheless, in contrast to our study, Yin et al [ 27 ] found in their collected Reddit data set that relationship and health testing were more often mentioned than ancestry testing.…”
Section: Discussionsupporting
confidence: 92%
“…However, our results did not show any specific topics on the educational content of DTC genetic testing. Considering that consumers in the United States continue to use DTC ancestry tests to prove their “genetic purity” and discriminate against marginalized ethnic groups such as the aforementioned ones, especially on social media [ 17 , 18 ], research has called for more educational content and scientific explanations about DTC genetic testing [ 20 , 21 ]. Despite finding some videos expressing concerns toward DTC genetic testing (eg, documentaries), the majority of the videos seem to fail to highlight the advantages as well as the disadvantages and risks of DTC genetic testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While science communication literature calls on communicators and audiences to interact and build relationships on social media ( Taylor and Kent, 2014 ; Avidar et al, 2015 ), there is still a lack of research on the predictors of audience dissemination. Previous research related to social media focuses mostly on scientists’ motivation for choosing online platforms ( Poliakoff and Webb, 2007 ; Mewburn and Thomson, 2013 ; Jia et al, 2017 ), how effectively science institutions are using social media ( Lee and VanDyke, 2015 ; Lee et al, 2018 ), core topics around scientific issues ( Pearce et al, 2014 ; Büchi, 2017 ; Lee et al, 2020 ), audience’s trust in online science content ( Liang et al, 2014 ; Huber et al, 2019 ) as well as the extent to which audiences use social media ( Anderson et al, 2010 ; Su et al, 2015 ; Hargittai et al, 2018 ). However, little has examined audience’s SSC behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These variables afforded the opportunity to examine and compare the influence of traditional product promotion (message sidedness) and communication of scientific risk (hedging) in a DTC health product context. Previous research in this area analyzed social media content from 23andMe to understand how the popular DTC genetic testing company balances promotional and science content [8]. Still, scholars have called for more research examining communication strategies used in for-profit science communication [9] and there are opportunities to examine the processes and effects of how message strategies may influence consumers' perceptions and purchase intentions related to DTC genetic testing.…”
Section: Introductionmentioning
confidence: 99%